Contemporary issues of equity in education - Gannon, Susanne; Sawyer, Wayne (Cambridge Scholars Publishing, 2014)
Contemporary Issues of Equity in Education argues that equity and social justice must be brought back to the centre of discussions about education. It traces international, system-wide and local effects of policies that increase marketization and competition between students, schools and systems, whilst erasing wider considerations of the socio-cultural contexts that shape educational experiences and outcomes. Leading researchers interrogate the design of educational systems for social justic ...